Coupled valence band dispersions and the quantum defect of excitons in Cu2O. (1st June 2016) - Schöne, Florian; Krüger, Sjard-Ole; Grünwald, Peter; Aßmann, Marc; Heckötter, Julian; Thewes, Johannes; Stolz, Heinrich; Fröhlich, Dietmar; Bayer, Manfred; Scheel, Stefan
Abstract: Recent high-resolution absorption spectroscopy on highly excited excitons in cuprous oxide (Kazimierczuk et al 2014 Nature 514 343–347 ) have revealed significant deviations of their spectrum from the ideal hydrogen-like series. In atomic physics, the influence of the ionic core and the resulting modifications of the Coulomb interaction are accounted for by the introduction of a quantum defect. Here we translate this concept to the realm of semiconductor physics and show how the complex band dispersion of a crystal is mirrored in a set of empirical parameters similar to the quantum defect in atoms. Experimental data collected from high-resolution absorption spectroscopy in electric fields allow us to compare results for multiple angular momentum states of the yellow and even the green exciton series of Cu 2 O . The agreement between theory and experiment validates our assignment of the quantum defect to the nonparabolicity of the band dispersion.